EUROPEAN FOOD SAFETY AUTHORITY AND THE JUDICIAL REVIEW OF ITS SCIENTIFIC OPINIONS AND ADMINISTRATIVE ACTS - Oana ŞARAMET; A. TOMA-BIANOV (Bulletin of the Transilvania University of Braov • Vol. 4 (53) •No. 2 - 2011 Series VII: Social Sciences • Law, 2011)
The main goal of this paper is to provide a narrative account of the historical evolution of European Food Safety Authority and of EFSA’s role in regulating European Union Food Law. Although EFSA hasn’t been vested with regulatory power, its scientific opinions are likely to acquire a de facto legal binding value for the European Commission or Member States’ legislative authorities when regulating. In this context, this paper also questions if EFSA’s scientific opinions and administrative acts may be challenged before European Courts.
Keywords: European Union; EFSA; food safety